Effects of interferon-?2b on hearing - Kaygusuz, I; Kaygusuz, TÖ; Öztürk, A; Kiliç, SS; Karlidag, T; Keles, E; Yalçin, S (B C Decker Inc, 2004)
The aim of the present study was to investigate the effects of interferon-alpha2b treatment on hearing in patients with chronic active hepatitis B. Twenty-six patients with chronic active hepatitis B were enrolled in the study, and pure-tone audiometry was performed to determine hearing thresholds of the patients before and at the end of 6 months of interferon-alpha2b treatment. There was no significant change in hearing thresholds of patients after treatment with interferon-alpha2b (p>0.05). The results of the present study indicate that interferon-aalpha2b therapy does not have any negative effect on hearing thresholds of patients with chronic active hepatitis B. There is a need for further studies involving larger numbers of patients to allow conclusions to be drawn regarding the safety of this therapy with respect to hearing.
Keywords: interferon; hearing loss; audiometry